Social Functioning of Women with Turner Syndrome - Zadrożna, Ilona (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
The article concerns social functioning of women with Turner syndrome, focusing particularly on their family life (relations with parents, siblings, partner and children), and relations with others (friends, acquaintances, workmates and members of TS support organizations). The author also tries to find correlations between growth hormone treatment, sex hormones treatment, age of TS diagnosis, karyotype and social functioning of TS women. Turner Syndrome is a quite common (1 in every 2500 live female births) human genetic disorder which affects only females. Females with TS lack all or part of one of two sex X chromosomes. The phenotype of TS women includes short stature and ovarian failure (which usually causes infertility) specific anatomic abnormalities (such as a short neck with a webbed appearance, a low hairline at the back of the neck, and low-set ears) and characteristic neurocognitive profile, which usually does not include mental retardation. The treatment of TS girls includes growth hormone and sex hormones therapy. 71 women took part in the study (30 from Poland and 41 from other countries – USA, Australia and United Kingdom). Researches indicated that generally women with TS showed relatively good functioning in relations in family of origin (with parents and siblings) and in social environment (quite high professional activity, good functioning in relations with friends and acquaintances). Relations with parents, especially with mothers, were usually very close, but often revealed overprotective parents’ attitude towards TS women (even in their adult life). Relations with fathers were slightly worse, more often revealing lack of fathers’ acceptance towards TS women. Relations with siblings were rather close, but again revealed overprotective siblings’ attitude towards TS sisters. Researches also revealed relatively weak functioning of TS women in relations in family of procreation (with partner and children).